HDA6-dependent histone deacetylation regulates mRNA polyadenylation in Arabidopsis - Lin, Juncheng; Hung, Fu-Yu; Ye, Congting; Hong, Liwei; Shih, Yuan-Hsin; Wu, Keqiang; Li, Qingshun Q. (Genome Research, 2020)
Eukaryotic histone deacetylation, critical for maintaining nucleosome structure and regulating gene expression, is mediated by histone deacetylases (HDACs). Although nucleosomes have been reported to regulate mRNA polyadenylation in humans, the role of HDACs in regulating polyadenylation has not been uncovered. Taking advantage of phenotypic studies on Arabidopsis, HDA6 (one of HDACs) was found to be a critical part of many biological processes. Here, we report that HDA6 affects mRNA polyadenylation in Arabidopsis. Poly(A) sites of up-regulated transcripts are closer to the histone acetylation peaks in hda6 compared to the wild-type Col-0. HDA6 is required for the deacetylation of histones around DNA on nucleosomes, which solely coincides with up-regulated or uniquely presented poly(A) sites in hda6. Furthermore, defective HDA6 results in an overrepresentation of the canonical poly(A) signal (AAUAAA) usage. Chromatin loci for generating AAUAAA-type transcripts have a comparatively low H3K9K14ac around poly(A) sites when compared to other noncanonical poly(A) signal–containing transcripts. These results indicate that HDA6 regulates polyadenylation in a histone deacetylation–dependent manner in Arabidopsis.
10.1101/gr.255232.119